Picturebooks as objects - Kümmerling-Meibauer, Bettina (Array, 2019)
Based on recent studies on materiality, picturebook research, and cognitive studies, this paper investigates how children may perceive picturebooks as objects and their material properties. In this regard, we emphasise three dimensions of picturebooks as objects and relate them to developmental stages. The first dimension concerns the materials the picturebooks are composed of, such as paper, cardboard, wood, plastics, and cloth. The second dimension refers to the type of book, e.g. hardbacks, sets of cardboard sheets, fanfold books, pop-up books, and even hybrid objects such as books which are toys at the same time. Finally, this study focuses on the types of actions that are associated with picturebooks as objects, such as biting, building, piling up, setting up, painting, collecting, and arranging. In sum, we argue that an examination of the cognitive perspective is fundamental for the investigation of the social and cultural aspects of the materiality of picturebooks.